Religion-State Relations in the United States and Germany: The Quest for Neutrality - Albert, Richard (A journal of church and state, 2014)
The relationship between church and state in the United States and Germany has been the subject of important scholarly treatments from law, history, theology, sociology, and political science. The most clarifying contributions have often combined two or more of these perspectives to illuminate a discrete question on the boundary separating religion from government.